Broadcasting messages securely in VANET - Miyara, Mounia; Toulni, Hamza; Nsiri, Benayad (International Journal of Engineering and Technology, 2019)
In Vehicular Ad hoc Networks, the secure sharing of information exchanged is necessary, due to the importance and sensitivity of this information exchanged. But the features and requirements of VANET prevent direct application of existing security solutions impossible. In this paper, we propose an effective solution to ensure the security of critical and urgent information. The solution provides authentication and confidentiality while minimizing the time required to decrypt the messages.Â Â